2012
DOI: 10.1371/journal.pone.0048788
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus, Human Papillomavirus and Mouse Mammary Tumour Virus as Multiple Viruses in Breast Cancer

Abstract: BackgroundThe purpose of this investigation is to determine if Epstein Barr virus (EBV), high risk human papillomavirus (HPV), and mouse mammary tumour viruses (MMTV) co-exist in some breast cancers.Materials and MethodsAll the specimens were from women residing in Australia. For investigations based on standard PCR, we used fresh frozen DNA extracts from 50 unselected invasive breast cancers. For normal breast specimens, we used DNA extracts from epithelial cells from milk donated by 40 lactating women. For i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
153
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(169 citation statements)
references
References 37 publications
12
153
2
2
Order By: Relevance
“…2016; 11(3):e34806. (11,18,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53). Table 1 shows a summary of the EBV-DNA positive subjects according to nationality, types of sample, and kinds of control tissue in the 20 selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…2016; 11(3):e34806. (11,18,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53). Table 1 shows a summary of the EBV-DNA positive subjects according to nationality, types of sample, and kinds of control tissue in the 20 selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…3 Several other recent studies, including 3 from the Middle East, showed clearly that EBV is present in 30-50% of human breast cancer. [4][5][6][7][8] Overall, these studies demonstrate that EBV is present in human breast cancer; given the biological actions of EBV-derived onco-proteins, it is quite possible that it plays an important role in the initiation and/or progression of this malignancy. This is based on our study as well as recent investigations about the role of LMP1 and EBNA1 onco-proteins of EBV in the initiation of epithelialmesenchymal transition (EMT) in human nasopharyngeal cancer.…”
mentioning
confidence: 76%
“…3,11,13 This is, to the best of our knowledge, the first report on the co-presence of EBV and high-risk HPVs in human breast cancer and the relation of this co-incidence with cancer phenotype in the Middle East area using 2 methodologies, PCR and IHC (Table 1A and 1B). In fact, there are only 6 investigations worldwide regarding the co-presence of EBV and high-risk HPVs in human breast cancer: one from Australia, 7 one from Chile, 17 one from China, 18 2 from Taiwan 19,20 and one from the USA. 21 Five among these studies confirmed the presence of both EBV and HPVs in breast cancer using mainly PCR analysis; 7,17,18,19,20 however one study could not confirm this statement in which the authors used RNA-Sequencing analysis to detect the presence of these viruses.…”
mentioning
confidence: 99%
“…Esta frecuencia de coinfección es intermedia con respecto a la reportada en otros estudios internacionales, en los cuales oscila entre el 2.1 y el 38% 20,31 . Es importante destacar que son pocos los estudios que han evaluado la presencia de este virus en Sudamérica.…”
Section: Discussionunclassified
“…A pesar de que el VEB se asocia con frecuencia con neoplasias linfoides humanas en pacientes inmunosuprimidos 18 , diversos estudios han demostrado que también existe una posible asociación con el desarrollo de malignidad en células epiteliales, como el tejido mamario, basándose principalmente en algunas observaciones que sustentan esta hipótesis: 1) la alta incidencia de cáncer de mama masculino en países del mediterráneo endémicos de VEB; 2) el desarrollo de linfomas asociados al VEB en las mamas; y 3) las similitudes morfológicas entre los carcinomas medulares de mama y los carcinomas nasofaríngeos 19 . La evidencia más específica de la asociación del VEB con el cáncer de mama ha sido la identificación de secuencias génicas del virus dentro de tumores mamarios 20,21 . Por otra parte, también se ha evaluado la expresión de proteínas latentes del VEB en líneas celulares de cáncer de mama in vitro e in vivo 22 , así como también la capacidad oncogénica de sus proteínas virales 6 .…”
Section: Introductionunclassified